2006
DOI: 10.1111/j.1530-0277.2006.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ethanol Responsive Domains of Adenylyl Cyclase

Abstract: The current study with mammalian ACs provides a new class of alcohol-responsive protein and possibly a new mechanism of alcohol action on cellular function. The identification of ethanol responsive domains will facilitate the elucidation of the mechanisms by which ethanol enhances the activity of AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 46 publications
7
43
0
1
Order By: Relevance
“…In contrast, in the case of ACs, there are relatively few studies on chimeras of full-length AC isoforms (Levin and Reed, 1995;Crossthwaite et al, 2005;Yoshimura et al, 2006;Diel et al, 2008). A major reason for this situation is the fact that the chimeras are unstable and, hence, functionally inactive (Seebacher et al, 2001).…”
Section: From Organs To Purified Adenylyl Cyclasesmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, in the case of ACs, there are relatively few studies on chimeras of full-length AC isoforms (Levin and Reed, 1995;Crossthwaite et al, 2005;Yoshimura et al, 2006;Diel et al, 2008). A major reason for this situation is the fact that the chimeras are unstable and, hence, functionally inactive (Seebacher et al, 2001).…”
Section: From Organs To Purified Adenylyl Cyclasesmentioning
confidence: 97%
“…Starting from the early observation that ethanol at clinically relevant concentrations increases AC activity in mouse striatal membranes (Hoffman and Tabakoff, 1982), subsequent studies revealed that AC7 is particularly sensitive to stimulation by ethanol and that the effects of ethanol are mediated via the cytosolic domains (Yoshimura and Tabakoff, 1999;Yoshimura et al, 2006;Kou and Yoshimura, 2007;Dokphrom et al, 2011). Female mice with reduced AC7 levels show increased alcohol consumption, whereas increased AC7 levels lead to elevated ethanol-induced adrenocorticotropin and corticosterone levels (Pronko et al, 2010;Desrivieres et al, 2011).…”
mentioning
confidence: 99%
“…But despite decades of investigation, the evidence is inconclusive for any specific molecular target for ethanol on any protein (for reviews see (6,7)). Many potential protein targets have been identified (4,8) including voltage-gated Na þ channels (9), adenylyl cyclase (10,11), guanine nucleotide binding protein G s (12), the GLT1 glutamate transporter (13), gap junctions (14), g-aminobutyric acid (GABA) A receptors (6), n-methyl-daspartate (NMDA) receptors (15), nicotinic acetylcholine receptor (nAChR) channels (16,17), and the cannabinoid receptor 1 (18). One system within the brain that appears to be sensitive to alcohol dependence is the endocannabinoid system (for review see (19)).…”
Section: Introductionmentioning
confidence: 99%
“…The boundaries of the C1a, C1b, and C2 domains are aa197-aa454, aa455-aa595, and aa864-aa1080, respectively, according to the human AC7 protein (NP_001105.1). The AC7-2C1aN construct was a gift from Dr. Masami Yoshimura (Yoshimura et al, 2006). The constructs containing the NAAIRS (AsnAla-Ala-Ile-Arg-Ser) sequence were generated by site-directed mutagenesis PCR of the targeted regions followed by cloning of the mutated fragments into pFBneo-AC7-myc vector using two unique restriction enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…3). Replacing the C1 domain of AC7 with that of AC2 resulted in an inactive enzyme (unpublished data; Yoshimura et al, 2006). Replacing the membrane domains of AC7 with those of AC2 yielded a functional cyclase, AC7-2M1-2M2.…”
Section: Regulation Of Adenylyl Cyclase VII By G 13mentioning
confidence: 99%